2022
DOI: 10.1002/cctc.202200867
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Selective Ring‐opening Terpolymerisation Facilitates Higher Order Switchable Catalysis

Abstract: Sequence selective ring‐opening terpolymerisation (ROTERP) allows the design of block polymerisation cascades with three distinct mechanistic cycles. Ring‐opening polymerisation (ROP), ring‐opening copolymerisation (ROCOP) and ROTERP can be combined in cascades where the onset of the most complex process supresses the occurrence of the simpler ones. The cascades furthermore enable the incorporation of different heteroallenes between blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…41,[46][47][48] Combining these ROCOPs, we recently reported a lithium catalysed PTA/CS 2 /epoxide ring-opening terpolymerisation (ROTERP, with propylene oxide (PO) or butylene oxide (BO)) and observed the formation of poly(ester-alt-ester-alttrithiocarbonates) with a few erroneous thioester links (Figure 1). [49][50][51] The ROTERP polymers were produced in an unusual (head-to-head)-alt-(tail-totail) regioselectivity meaning that the trithiocarbonate links sit adjacent to secondary CH 2 groups while the ester links sit adjacent to tertiary CH groups. This regioselectivity pointed towards a close mechanistic relation to Werner's CS 2 /epoxide ROCOP (ESI Figure S1) which led us to propose the reaction mechanism displayed in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,[46][47][48] Combining these ROCOPs, we recently reported a lithium catalysed PTA/CS 2 /epoxide ring-opening terpolymerisation (ROTERP, with propylene oxide (PO) or butylene oxide (BO)) and observed the formation of poly(ester-alt-ester-alttrithiocarbonates) with a few erroneous thioester links (Figure 1). [49][50][51] The ROTERP polymers were produced in an unusual (head-to-head)-alt-(tail-totail) regioselectivity meaning that the trithiocarbonate links sit adjacent to secondary CH 2 groups while the ester links sit adjacent to tertiary CH groups. This regioselectivity pointed towards a close mechanistic relation to Werner's CS 2 /epoxide ROCOP (ESI Figure S1) which led us to propose the reaction mechanism displayed in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…1). [49][50][51] The ROTERP polymers were produced in an unusual (head-to-head)-alt-This journal is © The Royal Society of Chemistry 2023 (tail-to-tail) regioselectivity meaning that the trithiocarbonate links sit adjacent to secondary CH 2 groups while the ester links sit adjacent to tertiary CH groups. This regioselectivity pointed towards a close mechanistic relation to Werner's CS 2 / epoxide ROCOP (ESI † Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Notably this sideprocess extends to related polymerisations and causes linkage scrambling and small molecule byproducts. [39][40][41][42][43][44][45][46] Previously it has been shown for alloxygen ROCOP that cooperative catalysts can control the reactivity of alkoxide intermediates and limit or even productively regulate side reactions. [47][48][49][50][51][52][53][54] Williams and co-workers in particular showed that a heterobimetallic Co(III)K catalyst can limit back-biting side reactions originating form alkoxides in CO2/epoxide ROCOP which lead to excellent polymer and linkage selectivities.…”
Section: B) Polymers Comprising Different Mono-(-o-c(=s)-o-oso O-c(=o...mentioning
confidence: 99%
“…41,[46][47][48] Combining these ROCOPs, we recently reported a Lithium catalysed PTA/CS2/epoxide ringopening terpolymerisation (ROTERP, with propylene oxide (PO) or butylene oxide (BO)) and observed the formation of poly(ester-alt-ester-alttrithiocarbonates) with a few erroneous thioester links (Figure 1). [49][50][51] The ROTERP polymers were produced in an unusual (head-to-head)-alt-(tail-totail) regioselectivity meaning that the trithiocarbonate links sit adjacent to secondary CH2 groups while the ester links sit adjacent to tertiary CH groups. This regioselectivity pointed towards a close mechanistic relation to Werner's CS2/epoxide ROCOP (ESI Figure S1) which led us to propose the reaction mechanism displayed in 4) also generates a link resulting from an isomerised epoxide (akin a virtual thiirane; A' in Figure 1) and an orthoterephtalate link in which both esters sit adjacent to tertiary CH "head" groups of the ring-opened monosubstituted epoxides.…”
Section: Introductionmentioning
confidence: 99%